HUBUNGAN ANTARA DUKUNGAN SOSIAL DENGAN TINGKAT KECEMASAN PERAWAT TERINFEKSI VIRUS COVID-19 - Dwi Riski Cahyani; Kurniati Zainuddin; Ahmad Ridfah (Jurnal Online Keperawatan Indonesia, 2022)
Anxiety is a individual reaction to unexpected events. The factors that may affect the anxiety level of nurses infected with the Covid-19 virus is perceived social support. The aim of this study was to find relationship between social support and the anxiety level of nurses infected with the Covid-19 virus. This is a quantitative study. Collecting data in this study was taken through distributing questionnaires. Applying total sampling technique to assemble 84 nurses at RS Bhayangkara Makassar. The hypothesis was statistically tested using Spearman rho. The result of statistical test (r = -0,790; p = 0,000; p < 0,05) reveals a negative relation between social support and the anxiety level of nurses infected with the Covid-19 virus. Based on the results of hypothesis testing in this study, it shows that there is a very significant negative relationship between social support and the anxiety level of nurses infected with the Covid-19 virus. The researcher submits suggestions to future researchers who wish to conduct research related to anxiety and social support should pay attention to the years of service that will be the subject of the study.